Public debt and interest rate spread in the European Union - Kersan-Škabić, Ines (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The goal of this paper is to assess the debt sustainability in the EU measuring the impact of public debt on the interest rate spreads. The results show that public debt has positive and significant influence on interest rate spreads but its influence is not the same for all observed groups of countries within the EU. The highest influence is in the Eurozone countries and in the group of peripheral EU countries (that are most affected by crisis: Portugal, Italy, Ireland, Greece and Spain). The lowest impact of public debt on interest rate spread is registered in non-Eurozone countries. Other important variables in explanation of interest rate spread are inflation differentials, FDI inflows, current account deficit and GDP growth rate
Argument Oeconomica, 2016, Nr 1 (36), s. 5-29
Keywords: public debt; European Union; interest rate spread; panel data analysis